Poststretch isometric contractions of the hamstrings: Just a brief stretch to achieve supramaximal isometric force - Chapman, N.; Whitting, J. W.; Broadbent, S.; Crowley-McHattan, Z.; Meir, R. (Journal of Applied Biomechanics, 2021)
Hamstring strain injuries are common in sport. Supramaximal eccentric or high-intensity isometric contractions are favored in hamstring strain injury prevention. The effect of combining these contraction modes in such prevention programs as a poststretch isometric contraction is unknown. Poststretch isometric contractions incorporate an active stretch and result in greater final isometric force than isometric contractions at comparable joint angles. This study compared torque and muscle activation levels between maximal voluntary isometric contraction and maximal poststretch isometric contractions of the knee flexors. Participants (n = 9) completed baseline maximal voluntary isometric contraction at 150° knee flexion and maximal poststretch isometric contractions at 120° knee flexion actively stretching at 60°/s to 150° knee flexion for final isometric contraction. Torque of the knee flexors and surface electromyography root mean square (sEMGRMS) of biceps femoris long head were simultaneously recorded and compared between baseline and poststretch isometric at 150° knee flexion. Torque was 14% greater in the poststretch isometric condition compared with baseline maximal voluntary isometric contraction (42.45 [20.75] N·m, 14% [22.18%], P < .001) without increase in sEMGRMS of biceps femoris long head (-.03 mV, ±.06, P = .130, d = .93). Poststretch isometric contractions resulted in supramaximal levels of poststretch isometric torque without increased activation of biceps femoris long head.